0383 Effects Of Resistance Exercise And Stretching On Sleep Of Patients With Chronic Insomnia. (27th April 2018) - D'Aurea, C V; Passos, G S; Santana, M G; Youngstedt, S D; Poyares, D; De Souza, A A; Bicudo, J; Tufik, S; De Mello, M T
Abstract: Introduction: Commonly chronic insomnia is treating with sleeping pills, which are associated adverse side effects, tolerance, and mortality. Thus, many nonpharmacological therapies have been studied. Regular exercise and stretching are possible nonpharmacological interventions to improve sleep quality. The propose of this study was to assess the effects of resistance exercise and stretching on insomnia severity and objective and subjective sleep in patients with chronic insomnia. Methods: Three 4-month treatments were compared: resistance exercise (n=10), stretching (n=10) and control (n=8). Resistance exercise occured at 50–60% 1-RM. Each session included 4 exercises for upper limbs: biceps, triceps, back, and pectorals; 4 exercises for lower limbs: flexors, extensors, abductors, and adductors; 1 trunk flexion exercise for abdominal area; and 1 trunk extension exercise. Stretching was low-intensity, involving the upper and lower limbs, with 8–10 types for each body region. Both treatments occurred 3 times/week from 5–6 p.m. Sleep was evaluated by polysomnography (PSG), actigraphy and questionnaires (Insomnia Severity Index - ISI and Pittsburgh Sleep Quality Index -PSQI). Results: Analysis of covariance (covariate control for baseline) revealed significant differences comparing resistance exercise and stretching with the control treatment for changes in ISI (-10.5 ± 2.3, -8.1 ± 2.0 vs 2.3 ± 1.8, respectively), total sleep time (31.6 ± 9.9, 23.5 ± 19.3 vs -21.4 ± 18.7 min), sleep onset latency (-7.1 ± 4.6, -5.2 ± 1.9 vs 2.2 ± 2.1 min), wake after sleep onset (-9.3 ± 2.8, -7.1 ± 3.0 vs 3.6 ± 4.2 min) and sleep efficiency - SE (4.4 ± 1.8, 5.0 ± 0.8 vs -2.3 ± 2.0%) evaluated by wrist actigraphy. PSQI global score (-5.3 ± 0.8, -3.9 ± 1.5 vs -0.1 ± 0.8), sleep duration (1.2 ± 0.3, 1.6 ± 0.6 vs -0.1 ± 0.2 h) also improved in both treatment groups compared with control. Sleep latency decreased after resistance exercise compared with control (-47.5 ± 15.0 vs -15.6 ± 18.4 min) and sleep efficiency increased after resistance exercise compared with control (19.5 ± 3.9 vs 2.1 ± 4.3%). No differences were observed in the PSG, except REM latency that decreased after stretching compared with resistance exercise and control (-41.0 ± 23.1 vs 21.5 ± 24.0 and 24.5 ± 21.7 min). Conclusion: Moderate-intensity resistance exercise or stretching decreased insomnia severity and improved objective and subjective sleep in patients with chronic insomnia. Support (If Any): Research supported by CEPID/FAPESP, AFIP and CEPE.